Obtenção de fermento lático endógeno para produção de queijo típico da mesorregião sudoeste do Paraná - Todescatto, Carla (2014)
The Greater Region Southwest of Paraná stands out for dairy farming, with production, processing and trading of derivatives. The use of endogenous lactic acid bacteria is gaining global market research and product development is attracting the interest of Educational Institutions in Brazil. This work aimed to isolate, identify and characterize the lactic microflora of raw milk, to develop endogenous starter culture, and using it, prepare the Cheese Typical. Two starters cultures, Streptococcus thermophillus compounds by bacteria and Lactobacillus delbrueckii sp bulgaricus were developed. The starter culture were tested in two dairy region, using pasteurized milk, preservatives sodium nitrate and lysozyme enzyme. The elaborate cheeses were subjected to analysis for the monitoring of changes during maturation (30, 60 and 180 days) and all samples exhibited physicochemical and microbiological characteristics according to Brazilian legislation. They can be classified broadly as cheese medium humidity ranging from 40.71 to 42.44 g/100 g (30 days), from 35.37 to 40.28 g/100 g (60 days), and from 33.63 to 38.63 g/100 g (180 days), according to the content of fatty matter in dry matter, cheeses can be classified as fat, from 40.37 to 48.80 (30 days), from 44.42 to 48.25 (60 days) and 45.30 to 49.80 (180 days). Proteins ranged from 20.57 to 23.95 g/100 g (30 days), from 21.88 to 24.71 g/100 g (60 days), from 23.52 to 30.57 g/100 g (180 days), lipids between 20.57 to 23.95 g/100 g (30 days), from 24.71 to 21.88 g/100 g (60 days), and from 30.57 to 23.52 g/100 g (180 days). The ash content ranged from 2.99 to 4.88 (30 days), from 4.10 to 5.00 (60 days) and from 4.58 to 5.19 (180 days) the water activity from 0.9531 to 0.9635 (30 days), 0.9366 to 0.9547 (60 days) and 0.9284 to 0.9380 (180 days). Textural analyzes indicated that the cheese developed during periods of maturation, showed an increase in hardness, where the lowest value at 30 days was at 18377.19 g passing the 180 days to a maximum value of 27401 g. The elasticity at 30 days showed that in 0.82, went 0.88 at 180 days. The chewiness of 11412.92 (30 days) increased to 5116.76 (180 days). The cohesiveness of 0.67 (30 days) stood at 0.20 (180 days). The adhesiveness which was -205.45 (30 days) increased to -25.04 (180 days) and the resistivity which was initially 0.21 (30 days) was 0.04 (180 days). Regarding the analysis of the samples showed high color brightness (L*), coming to have 180 days (73.51 ± 3.62 to 79.75 ± 0.56), with a predominance of yellow component (b*) (34.10 ± 0.55 to 36.81 ± 0.29), and samples within the green spectrum (a*) (-7.40 ± 0.06 and -7.82 ± 0.21), showed minor variations. The sensory analysis of Cheese Typical pointed to acceptance by the panelists. This work represents one of the steps of using endogenous starter culture in a cheese, which was called as "Santo Giorno", and contributed to understanding the variations and interactions of physico-chemical and microbiological development of a regional product, with high quality components.